Enhancing sustainability: Composite materials from recycled HDPE and denim fillers - Webo, Wilson; Khoathane, Moshibudi Caroline; Mhike, Washington; Mohlamonyane, Raymond Segoboge (Polymer engineering and science, 2025)
This study examines the mechanical and thermal properties of a sustainable composite material made from recycled high‐density polyethylene (HDPE), denim fibers, and maleic anhydride polypropylene (MAPP). The influence of denim filler volume fractions (0%–20%) on tensile strength, stiffness, and thermal stability is evaluated. Tensile strength and stiffness increase significantly with higher filler content, reaching 30 MPa and 1,000,000 N/m, respectively, at a 20% filler volume fraction. However, elongation at fracture declines sharply, indicating reduced ductility. Thermogravimetric analysis shows decreased thermal stability with increasing denim content, while differential scanning calorimetry reveals reductions in melting and crystallization temperatures. Fourier‐transform infrared spectroscopy confirms MAPP's role in enhancing fiber–matrix adhesion. While this study maintains a fixed MAPP content of 5%, its influence on composite properties highlights the need for future studies exploring variable concentrations. These findings underline the composite's potential for structural applications requiring strength and rigidity but limited thermal stability. Highlights Recycled HDPE and denim fibers are used to create a sustainable composite. MAPP enhances fiber–matrix adhesion, improving mechanical properties. Increased denim content raises stiffness and tensile strength but reduces ductility. Denim fibers reduce thermal stability and crystallinity of the composite. The composite is ideal for structural applications prioritizing rigidity. Sustainable recycling of denim waste into polymer composites: A lifecycle approach to material transformation, performance enhancement and potential applications to manufacturing.